Challenges and importance of formulae equating catecholamine and non-catecholamine vasoconstrictor dosages - Wieruszewski, Patrick M.; Khanna, Ashish K. (Journal of critical care, 2021)
[...]30- and 90-day mortality ranges from 50 to 80% in septic shock patients who receive high-dose vasoconstrictors, defined as a specified threshold of norepinephrine equivalent [1]. [...]exact norepinephrine dosages were only reported for the first two hours, leaving the subsequent 4 h to be extrapolated from the provided figure, introducing inaccuracies. To arrive at a norepinephrine excess of 110 ng/kg/min, we estimate Goradia et al. assumed the mean body weight of the subjects was approximately 90 kg. [...]it is important to note that with every 10 kg difference in this weight assumption, the calculated conversion ratio differs by approximately 10%. [...]it is unclear what form the distribution of response to angiotensin II and vasopressin would take if the entire population—or at least the population with shock—was assessed as a whole.